Soil organic carbon, total nitrogen, available nutrients, and yield under different straw returning methods - Huang, Tiantian; Yang, Ning; Lu, Chen; Qin, Xiaoliang; Siddique, Kadambot H.M. (Soil & tillage research, 2021)
•Straw mulching (SM) and straw burying (SB) increase crop yields and soil nutrient contents.•SB is more conducive to increasing soil organic carbon, soil total nitrogen, and soil total potassium than SM.•SM is more conducive to increase soil available nitrogen, soil available phosphorus, and soil available potassium than SB.•SM performed better than SB in arid regions.•SB performed better than SM where mean annual precipitation is >800 mm. Straw returning is an important measure for improving soil organic matter, biological activity, and nutrient availability. Straw mulching and straw burying are two methods for returning straw to the soil; however, there is little information to compare their benefits and limitations. This study assessed changes in soil nutrients induced by straw mulching and straw burying using a meta-analysis of straw returning data from 420 publications in China. The results showed that straw burying significantly increased soil organic carbon (SOC), soil total nitrogen (STN), soil total phosphorus (STP), soil total potassium (STK), soil available nitrogen (SAN), soil available phosphorus (SAP), and soil available potassium (SAK) in the surface soil (0–20 cm), with mean effect sizes of 0.126, 0.095, 0.056, 0.053, 0.118, 0.117, 0.138, respectively. Straw mulching increased SOC, STN, STP, SAN, SAP, and SAK in the surface soil, with mean effect sizes of 0.114, 0.079, 0.082, 0.125, 0.152, 0.150, respectively. Straw burying is more conducive to increasing SOC, STN, and STK, while straw mulching is more conducive to increasing SAN, SAP, and SAK. Straw mulching increased soil nutrient contents more than straw burying in areas with mean annual precipitation (MAP) <400 mm, while the reverse was true in areas with MAP> 800 mm. Straw mulching and straw burying both increased crop yield, with mean effect sizes of 0.100 and 0.101, respectively. Straw burying positively correlated with the effect size of yield, SOC, SAP, and SAK, while there were no significant relationships for straw mulching. Long-term straw burying and straw mulching was conducive to increasing crop yields, SOC, and STN. The benefits and limitations of straw mulching and burying on soil fertility and yield vary under different agronomic management, environmental, and edaphic factors.